The strength of difference : itineraries of atypical bosses - Alter, Norbert (International perspectives on equality, diversity and inclusion ;, 2018)
Bosses and managers from atypical backgrounds have succeeded in avoiding socially pre-determined outcomes byturning their differences into resources. This did not, however, mean that theybecame "normal". They are leaders, but they remain excluded from convened socialpositions. This distance leads them to listen, to look upon, and toanalyse their environments, their pasts and their relations with others muchmore than "normal" people do. Furthermore, this distance facilitatesentrepreneurial risk-taking and the creation of networks, complicity andsolidarity. It requires the mobilization of extraordinary social intelligence. This book describes theprocesses through which stigma can be mastered, if not forgotten. It alsoexplains that the position of outsiders, in the broadest meaning of the term,translates the social experiences of all those who belong to several worlds,and who find themselves condemned simultaneously to engagement and detachment.